Carbon capture from ArcelorMittal hot briquetted Iron plant using air liquide cryocap™ FG technology – FEED study - Sebastiano Giardinella; Varun Gopalakrishnan; Vincent Gueret; Lindsey Turney; Vincent Lu; Chris Tovee; David Zybko; Marcelo Andrade; Christopher Harris; Pierre-Philippe Guerif; Timothy Henderson; Anderson Morelato; et al. (International Journal of Greenhouse Gas Control, 2026)

Determining the age of clonal plants: challenges and prospects - Jitka Klimešová; Patrik Mráz; Beata Oborny; Timothy Harris; Gabriela Santos da Silva; Alexandre Ferraro; Jiří Doležal; Mathieu Millan (Trends in Ecology & Evolution, 2026)

Vulnerability of marine megafauna to global at‐sea anthropogenic threats - Michelle VanCompernolle; Juliet Morris; Hannah J. Calich; Jorge P. Rodríguez; Sarah A. Marley; Jessica R. Pearce; Briana Abrahms; Katya Abrantes; André S. Afonso; Alex Aguilar; Andrews Agyekumhene; Tomonari Akamatsu; et al. (Conservation Biology, 2026)
Marine megafauna species are affected by a wide range of anthropogenic threats. To evaluate the risk of such threats, species’ vulnerability to each threat must first be determined. We build on the existing threats classification scheme and ranking system of the International Union for Conservation of Nature (IUCN) Red List of Threatened Species by assessing the vulnerability of 256 marine megafauna species to 23 at‐sea threats. The threats we considered included individual fishing gear types, climate‐change‐related subthreats not previously assessed, and threats associated with coastal impacts and maritime disturbances. Our ratings resulted in 70 species having high vulnerability ( v > 0.778 out of 1) to at least 1 threat, primarily drifting longlines, temperature extremes, or fixed gear. These 3 threats were also considered to have the most severe effects (i.e., steepest population declines). Overall, temperature extremes and plastics and other solid waste were rated as affecting the largest proportion of populations. Penguins, pinnipeds, and polar bears had the highest vulnerability to temperature extremes. Bony fishes had the highest vulnerability to drifting longlines and plastics and other solid waste; pelagic cetaceans to 4 maritime disturbance threats; elasmobranchs to 5 fishing threats; and flying birds to drifting longlines and 2 maritime disturbance threats. Sirenians and turtles had the highest vulnerability to at least one threat from all 4 categories. Despite not necessarily having severe effects for most taxonomic groups, temperature extremes were rated among the top threats for all taxa except bony fishes. The vulnerability scores we provide are an important first step in estimating the risk of threats to marine megafauna. Importantly, they help differentiate scope from severity, which is key to identifying threats that should be prioritized for mitigation.

The Toxicology Investigators Consortium 2024 Annual Report - Kim Aldy; Shao Li; Mari Costantini; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; Michael Abesamis; Faiz Ahmed; Salman Ahsan; Peter Akpunonu; Adam Algren; et al. (Journal of Medical Toxicology, 2026)

Autonomic neural control of motor activity in the intestine of freshwater barramundi (Lates calcarifer) - Hayley Rhodes; Lee Travis; Timothy J. Hibberd; Nick J. Spencer; James Harris (Cell and Tissue Research, 2026)
Evolutionary pressure on the gastrointestinal (GI) tract of teleost fish differs substantially from those of terrestrial animals. The intestine is a pivotal organ in teleost, for maintaining osmotic balance against the surrounding aquatic environment; primarily through its role in water absorption. Intestinal sensory and motor functions of vertebrates are largely mediated by the enteric nervous system (ENS) embedded within the gut wall. Although the ENS has been described in several teleost species, the group comprised of more than 25,000 species displays remarkable ecological, anatomical, and physiological diversity. As such, species that display distinct adaptations, i.e., euryhalinity, may provide valuable comparative insights. Here we show the structure of the ENS within the intestine of barramundi ( Lates calcarifer ), a catadromous perch species with a unique life history and growing commercial relevance. Immunohistochemical labelling identified enteric neurons synthesising nitric oxide synthase (NOS) and calcitonin-gene-related peptide (CGRP), both of which were typically uniaxonal with smooth cell bodies. Qualitatively, these neuronal populations formed a weakly arranged enteric plexus, analogous to the myenteric plexus found in terrestrial animals. Quantitatively, the proportion of NOS immunoreactive neurons decreased along the rostro-caudal axis of the intestine without accompanying changes to the overall neuronal density. Video imaging of intestinal wall movements ex vivo identified multiple recurrent motility patterns which were hexamethonium-sensitive, suggesting regulation by nicotinic synaptic transmission within enteric pathways. Together, these findings show that enteric neurons are present in the barramundi intestine but form a comparatively less defined plexus than in higher terrestrial vertebrates. These enteric neurons are involved in the regulation of intestinal motility via nicotinic transmission.

A conceptual framework for responding to cross-border climate change impacts - Sara Talebian; Magnus Benzie; Katy Harris; Łukasz Jarząbek; Piotr Magnuszewski; Timothy R. Carter; Noam Obermeister (Environmental Science & Policy, 2025)

Ocean crustal veins record dynamic interplay between plate-cooling-induced cracking and ocean chemistry - Aled D. Evans; Rosalind M. Coggon; Michelle Harris; Elliot J. Carter; Elmar Albers; Gilles M. Guérin; Thomas M. Belgrano; Mallika Jonnalagadda; Lewis J.C. Grant; Pamela D. Kempton; David J. Sanderson; James A. Milton; et al. (Earth and Planetary Science Letters, 2025)

Properties of outer solar system pebbles during planetesimal formation from meteor observations - Peter Jenniskens; Paul R. Estrada; Stuart Pilorz; Peter S. Gural; Dave Samuels; Steve Rau; Timothy M.C. Abbott; Jim Albers; Scott Austin; Dan Avner; Jack W. Baggaley; Tim Beck; et al. (Icarus, 2024)

Dominance and rarity in tree communities across the globe: Patterns, predictors and threats - Iris Hordijk; Lalasia Bialic‐Murphy; Thomas Lauber; Devin Routh; Lourens Poorter; Malin C. Rivers; Hans ter Steege; Jingjing Liang; Peter B. Reich; Sergio de‐Miguel; Gert‐Jan Nabuurs; Javier G. P. Gamarra; et al. (Global Ecology and Biogeography, 2024)
Aim Ecological and anthropogenic factors shift the abundances of dominant and rare tree species within local forest communities, thus affecting species composition and ecosystem functioning. To inform forest and conservation management it is important to understand the drivers of dominance and rarity in local tree communities. We answer the following research questions: (1) What are the patterns of dominance and rarity in tree communities? (2) Which ecological and anthropogenic factors predict these patterns? And (3) what is the extinction risk of locally dominant and rare tree species? Location Global. Time period 1990–2017. Major taxa studied Trees. Methods We used 1.2 million forest plots and quantified local tree dominance as the relative plot basal area of the single most dominant species and local rarity as the percentage of species that contribute together to the least 10% of plot basal area. We mapped global community dominance and rarity using machine learning models and evaluated the ecological and anthropogenic predictors with linear models. Extinction risk, for example threatened status, of geographically widespread dominant and rare species was evaluated. Results Community dominance and rarity show contrasting latitudinal trends, with boreal forests having high levels of dominance and tropical forests having high levels of rarity. Increasing annual precipitation reduces community dominance, probably because precipitation is related to an increase in tree density and richness. Additionally, stand age is positively related to community dominance, due to stem diameter increase of the most dominant species. Surprisingly, we find that locally dominant and rare species, which are geographically widespread in our data, have an equally high rate of elevated extinction due to declining populations through large‐scale land degradation. Main conclusions By linking patterns and predictors of community dominance and rarity to extinction risk, our results suggest that also widespread species should be considered in large‐scale management and conservation practices.

Tissue elements in co-occurring herbs scale mostly isometrically, but do different plant strategies play the same game? - Martin Bitomský; Timothy Harris; Jitka Klimešová (Plant and Soil, 2024)

Repeat treatment of organotypic airway cultures with ethyl methanesulfonate causes accumulation of somatic cell mutations without expansion of bronchial-carcinoma-specific cancer driver mutations - Yiying Wang; Yuan Le; Kelly L. Harris; Ying Chen; Xilin Li; Jennifer Faske; Rebecca A. Wynne; Roberta A. Mittelstaedt; Xuefei Cao; Jaime Miranda-Colon; Lana Elkins; Levan Muskhelishvili; et al. (Mutation Research - Genetic Toxicology and Environmental Mutagenesis, 2024)

Challenges in assessing and managing multi-hazard risks: A European stakeholders perspective - Robert Šakić Trogrlić; Karina Reiter; Roxana L. Ciurean; Stefania Gottardo; Silvia Torresan; Anne Sophie Daloz; Lin Ma; Noemi Padrón Fumero; Sharon Tatman; Stefan Hochrainer-Stigler; Marleen C. de Ruiter; Julius Schlumberger; et al. (Environmental Science & Policy, 2024)

Lifetime of cm-sized zodiacal dust from the physical and dynamical evolution of meteoroid streams - Peter Jenniskens; Stuart Pilorz; Peter S. Gural; Dave Samuels; Steve Rau; Timothy M.C. Abbott; Jim Albers; Scott Austin; Dan Avner; Jack W. Baggaley; Tim Beck; Solvay Blomquist; et al. (Icarus, 2024)

Corrigendum to “A systematic conservation plan identifying critical areas for improved chondrichthyan protection in South Africa” [Biol. Conserv. 284 (2023) 110163] - Nina Faure-Beaulieu; Amanda T. Lombard; Jennifer Olbers; Victoria Goodall; Charlene da Silva; Ryan Daly; Gareth Jordaan; Sven E. Kerwath; Alison Kock; Bruce Q. Mann; Taryn S. Murray; Patricia Albano; et al. (Biological Conservation, 2023)

A systematic conservation plan identifying critical areas for improved chondrichthyan protection in South Africa - Nina Faure-Beaulieu; Amanda T. Lombard; Jennifer Olbers; Victoria Goodall; Charlene da Silva; Ryan Daly; Gareth Jordaan; Sven E. Kerwath; Alison Kock; Bruce Q. Mann; Taryn S. Murray; Patricia Albano; et al. (Biological Conservation, 2023)

Farm size limits agriculture's poverty reduction potential in Eastern India even with irrigation-led intensification - Anton Urfels; Kai Mausch; Dave Harris; Andrew J. McDonald; Avinash Kishore; Balwinder-Singh; Gerardo van Halsema; Paul C. Struik; Peter Craufurd; Timothy Foster; Vartika Singh; Timothy J. Krupnik (Agricultural Systems, 2023)

Development of benchmark datasets for text mining and sentiment analysis to accelerate regulatory literature review - Leihong Wu; Si Chen; Lei Guo; Svitlana Shpyleva; Kelly Harris; Tariq Fahmi; Timothy Flanigan; Weida Tong; Joshua Xu; Zhen Ren (Regulatory Toxicology and Pharmacology, 2023)

Proceedings of the fifth international Molecular Pathological Epidemiology (MPE) meeting - Song Yao; Peter T. Campbell; Tomotaka Ugai; Gretchen Gierach; Mustapha Abubakar; Viktor Adalsteinsson; Jonas Almeida; Paul Brennan; Stephen Chanock; Todd Golub; Samir Hanash; Curtis Harris; et al. (Cancer Causes & Control, 2022)

Quantifying risks avoided by limiting global warming to 1.5 or 2 °C above pre-industrial levels - Rachel Warren; Oliver Andrews; Sally Brown; Felipe J. Colón-González; Nicole Forstenhäusler; David E. H. J. Gernaat; P. Goodwin; Ian Harris; Yi He; Chris Hope; Desmond Manful; Timothy J. Osborn; et al. (Climatic Change, 2022)
The Paris Agreement aims to constrain global warming to ‘well below 2 °C’ and to ‘pursue efforts’ to limit it to 1.5 °C above pre-industrial levels. We quantify global and regional risk-related metrics associated with these levels of warming that capture climate change–related changes in exposure to water scarcity and heat stress, vector-borne disease, coastal and fluvial flooding and projected impacts on agriculture and the economy, allowing for uncertainties in regional climate projection. Risk-related metrics associated with 2 °C warming, depending on sector, are reduced by 10–44% globally if warming is further reduced to 1.5 °C. Comparing with a baseline in which warming of 3.66 °C occurs by 2100, constraining warming to 1.5 °C reduces these risk indicators globally by 32–85%, and constraining warming to 2 °C reduces them by 26–74%. In percentage terms, avoided risk is highest for fluvial flooding, drought, and heat stress, but in absolute terms risk reduction is greatest for drought. Although water stress decreases in some regions, it is often accompanied by additional exposure to flooding. The magnitude of the percentage of damage avoided is similar to that calculated for avoided global economic risk associated with these same climate change scenarios. We also identify West Africa, India and North America as hotspots of climate change risk in the future.

Reproductive Biology of Female Pacific Halibut (Hippoglossus stenolepis) in the Gulf of Alaska - Teresa Fish; Nathan Wolf; Timothy Scott Smeltz; Bradley P. Harris; Josep V. Planas (Frontiers in Marine Science, 2022)
Developing a robust understanding of Pacific halibut reproductive biology is essential to understanding the different components (e.g. maturity) that determine the reproductive output of the species and, therefore, for estimating the relative female spawning biomass. With these, effective and proactive management strategies can be designed and implemented to face the large-scale environmental changes to which high-latitude spawning fish are particularly vulnerable. To date, reproductive studies of Pacific halibut have mainly focused on population or regional scales, leaving the specific details of organism-level reproductive development unexamined. The work described here aimed to address information gaps in Pacific halibut reproductive biology by conducting a detailed histological examination of temporal changes in ovarian development over an annual reproductive cycle with special attention to the use of biological indicators ( e.g. oocyte diameter, gonadosomatic index, hepatosomatic index, Fulton’s condition factor, somatic fat) in characterizing female developmental stages and reproductive phases. Our results provide a foundation for future studies directed at improving current maturity estimations by histological assessment and explore models that test the utility of biological indicators to predict maturity in this important fish species.

Promoting FAIR Data Through Community-driven Agile Design: the Open Data Commons for Spinal Cord Injury (odc-sci.org) - Abel Torres-Espín; Carlos A. Almeida; Austin Chou; J. Russell Huie; Michael Chiu; Romana Vavrek; Jeff Sacramento; Michael B. Orr; John C. Gensel; Jeffery S. Grethe; Maryann E. Martone; Karim Fouad; et al. (Neuroinformatics, 2022)
The past decade has seen accelerating movement from data protectionism in publishing toward open data sharing to improve reproducibility and translation of biomedical research. Developing data sharing infrastructures to meet these new demands remains a challenge. One model for data sharing involves simply attaching data, irrespective of its type, to publisher websites or general use repositories. However, some argue this creates a ‘data dump’ that does not promote the goals of making data Findable, Accessible, Interoperable and Reusable (FAIR). Specialized data sharing communities offer an alternative model where data are curated by domain experts to make it both open and FAIR. We report on our experiences developing one such data-sharing ecosystem focusing on ‘long-tail’ preclinical data, the Open Data Commons for Spinal Cord Injury (odc-sci.org). ODC-SCI was developed with community-based agile design requirements directly pulled from a series of workshops with multiple stakeholders (researchers, consumers, non-profit funders, governmental agencies, journals, and industry members). ODC-SCI focuses on heterogeneous tabular data collected by preclinical researchers including bio-behaviour, histopathology findings and molecular endpoints. This has led to an example of a specialized neurocommons that is well-embraced by the community it aims to serve. In the present paper, we provide a review of the community-based design template and describe the adoption by the community including a high-level review of current data assets, publicly released datasets, and web analytics. Although odc-sci.org is in its late beta stage of development, it represents a successful example of a specialized data commons that may serve as a model for other fields.

Linearized esculentin-2EM shows pH dependent antibacterial activity with an alkaline optimum - Erum Malik; David A. Phoenix; Timothy J. Snape; Frederick Harris; Jaipaul Singh; Leslie H. G. Morton; Sarah R. Dennison (Molecular and Cellular Biochemistry, 2021)
Here the hypothesis that linearized esculentin 2EM (E2EM-lin) from Glandirana emeljanovi possesses pH dependent activity is investigated. The peptide showed weak activity against Gram-negative bacteria (MLCs ≥ 75.0 μM) but potent efficacy towards Gram-positive bacteria (MLCs ≤ 6.25 μM). E2EM-lin adopted an α-helical structure in the presence of bacterial membranes that increased as pH was increased from 6 to 8 (↑ 15.5–26.9%), whilst similar increases in pH enhanced the ability of the peptide to penetrate (↑ 2.3–5.1 mN m − 1 ) and lyse (↑ 15.1–32.5%) these membranes. Theoretical analysis predicted that this membranolytic mechanism involved a tilted segment, that increased along the α-helical long axis of E2EM-lin (1–23) in the N → C direction, with − < µH > increasing overall from circa − 0.8 to − 0.3. In combination, these data showed that E2EM-lin killed bacteria via novel mechanisms that were enhanced by alkaline conditions and involved the formation of tilted and membranolytic, α-helical structure. The preference of E2EM-lin for Gram-positive bacteria over Gram-negative organisms was primarily driven by the superior ability of phosphatidylglycerol to induce α-helical structure in the peptide as compared to phosphatidylethanolamine. These data were used to generate a novel pore-forming model for the membranolytic activity of E2EM-lin, which would appear to be the first, major reported instance of pH dependent AMPs with alkaline optima using tilted structure to drive a pore-forming process. It is proposed that E2EM-lin has the potential for development to serve purposes ranging from therapeutic usage, such as chronic wound disinfection, to food preservation by killing food spoilage organisms.

Opportunities and challenges for herbaria in studying the spatial variation in plant functional diversity - Timothy Harris; Mark Mulligan; Neil Brummitt (Systematics and Biodiversity, 2021)

Using machine learning for model benchmarking and forecasting of depletion-induced seismicity in the Groningen gas field - Jan Limbeck; Kevin Bisdom; Fabian Lanz; Timothy Park; Eduardo Barbaro; Stephen Bourne; Franz Kiraly; Stijn Bierman; Chris Harris; Keimpe Nevenzeel; Taco den Bezemer; Jan van Elk (Computational Geosciences, 2021)
The Groningen gas field in the Netherlands is experiencing induced seismicity as a result of ongoing depletion. The physical mechanisms that control seismicity have been studied through rock mechanical experiments and combined physical-statistical models to support development of a framework to forecast induced-seismicity risks. To investigate whether machine learning techniques such as Random Forests and Support Vector Machines bring new insights into forecasts of induced seismicity rates in space and time, a pipeline is designed that extends time-series analysis methods to a spatiotemporal framework with a factorial setup, which allows probing a large parameter space of plausible modelling assumptions, followed by a statistical meta-analysis to account for the intrinsic uncertainties in subsurface data and to ensure statistical significance and robustness of results. The pipeline includes model validation using e.g. likelihood ratio tests against average depletion thickness and strain thickness baselines to establish whether the models have statistically significant forecasting power. The methodology is applied to forecast seismicity for two distinctly different gas production scenarios. Results show that seismicity forecasts generated using Support Vector Machines significantly outperform beforementioned baselines. Forecasts from the method hint at decreasing seismicity rates within the next 5 years, in a conservative production scenario, and no such decrease in a higher depletion scenario, although due to the small effective sample size no statistically solid statement of this kind can be made. The presented approach can be used to make forecasts beyond the investigated 5-years period, although this requires addition of limited physics-based constraints to avoid unphysical forecasts.

The global abundance of tree palms - Robert Muscarella; Thaise Emilio; Oliver L. Phillips; Simon L. Lewis; Ferry Slik; William J. Baker; Thomas L. P. Couvreur; Wolf L. Eiserhardt; Jens‐Christian Svenning; Kofi Affum‐Baffoe; Shin‐Ichiro Aiba; Everton C. de Almeida; et al. (Global Ecology and Biogeography, 2020)
Aim Palms are an iconic, diverse and often abundant component of tropical ecosystems that provide many ecosystem services. Being monocots, tree palms are evolutionarily, morphologically and physiologically distinct from other trees, and these differences have important consequences for ecosystem services (e.g., carbon sequestration and storage) and in terms of responses to climate change. We quantified global patterns of tree palm relative abundance to help improve understanding of tropical forests and reduce uncertainty about these ecosystems under climate change. Location Tropical and subtropical moist forests. Time period Current. Major taxa studied Palms (Arecaceae). Methods We assembled a pantropical dataset of 2,548 forest plots (covering 1,191 ha) and quantified tree palm (i.e., ≥10 cm diameter at breast height) abundance relative to co‐occurring non‐palm trees. We compared the relative abundance of tree palms across biogeographical realms and tested for associations with palaeoclimate stability, current climate, edaphic conditions and metrics of forest structure. Results On average, the relative abundance of tree palms was more than five times larger between Neotropical locations and other biogeographical realms. Tree palms were absent in most locations outside the Neotropics but present in >80% of Neotropical locations. The relative abundance of tree palms was more strongly associated with local conditions (e.g., higher mean annual precipitation, lower soil fertility, shallower water table and lower plot mean wood density) than metrics of long‐term climate stability. Life‐form diversity also influenced the patterns; palm assemblages outside the Neotropics comprise many non‐tree (e.g., climbing) palms. Finally, we show that tree palms can influence estimates of above‐ground biomass, but the magnitude and direction of the effect require additional work. Conclusions Tree palms are not only quintessentially tropical, but they are also overwhelmingly Neotropical. Future work to understand the contributions of tree palms to biomass estimates and carbon cycling will be particularly crucial in Neotropical forests.

Changes in the orientations of cellulose microfibrils during the development of collenchyma cell walls of celery (Apium graveolens L.) - Da Chen; Laurence D. Melton; Duncan J. McGillivray; Timothy M. Ryan; Philip J. Harris (Planta, 2019)

Estimating aboveground net biomass change for tropical and subtropical forests: Refinement of IPCC default rates using forest plot data - Daniela Requena Suarez; Danaë M. A. Rozendaal; Veronique De Sy; Oliver L. Phillips; Esteban Alvarez‐Dávila; Kristina Anderson‐Teixeira; Alejandro Araujo‐Murakami; Luzmila Arroyo; Timothy R. Baker; Frans Bongers; Roel J. W. Brienen; Sarah Carter; et al. (Global Change Biology, 2019)
As countries advance in greenhouse gas (GHG) accounting for climate change mitigation, consistent estimates of aboveground net biomass change (∆AGB) are needed. Countries with limited forest monitoring capabilities in the tropics and subtropics rely on IPCC 2006 default ∆AGB rates, which are values per ecological zone, per continent. Similarly, research into forest biomass change at a large scale also makes use of these rates. IPCC 2006 default rates come from a handful of studies, provide no uncertainty indications and do not distinguish between older secondary forests and old‐growth forests. As part of the 2019 Refinement to the 2006 IPCC Guidelines for National Greenhouse Gas Inventories, we incorporate ∆AGB data available from 2006 onwards, comprising 176 chronosequences in secondary forests and 536 permanent plots in old‐growth and managed/logged forests located in 42 countries in Africa, North and South America and Asia. We generated ∆AGB rate estimates for younger secondary forests (≤20 years), older secondary forests (>20 years and up to 100 years) and old‐growth forests, and accounted for uncertainties in our estimates. In tropical rainforests, for which data availability was the highest, our ∆AGB rate estimates ranged from 3.4 (Asia) to 7.6 (Africa) Mg ha −1 year −1 in younger secondary forests, from 2.3 (North and South America) to 3.5 (Africa) Mg ha −1 year −1 in older secondary forests, and 0.7 (Asia) to 1.3 (Africa) Mg ha −1 year −1 in old‐growth forests. We provide a rigorous and traceable refinement of the IPCC 2006 default rates in tropical and subtropical ecological zones, and identify which areas require more research on ∆AGB. In this respect, this study should be considered as an important step towards quantifying the role of tropical and subtropical forests as carbon sinks with higher accuracy; our new rates can be used for large‐scale GHG accounting by governmental bodies, nongovernmental organizations and in scientific research.

Important Plant Areas: revised selection criteria for a global approach to plant conservation - Iain Darbyshire; Seona Anderson; Anna Asatryan; Andrew Byfield; Martin Cheek; Colin Clubbe; Zeineb Ghrabi; Timothy Harris; Charlie D. Heatubun; James Kalema; Sékou Magassouba; Ben McCarthy; et al. (Biodiversity and Conservation, 2017)

Molecular identification of the precise geographic origins of an invasive shrimp species in a globally significant Australian biodiversity hotspot - Annique Harris; Timothy J. Page; Seema Fotedar; Rodney Duffy; Michael Snow (Biological Invasions, 2017)

Pattern scaling using ClimGen: monthly-resolution future climate scenarios including changes in the variability of precipitation - Timothy J. Osborn; Craig J. Wallace; Ian C. Harris; Thomas M. Melvin (Climatic Change, 2016)

Evidence of endoplasmic reticulum stress and liver inflammation in the American mink Neovison vison with benign hepatic steatosis - Kirsti Rouvinen-Watt; Catherine Pal; Timothy Martin; Lora Harris; Tessema Astatkie; Darya Kryzskaya; Vesa Kärjä; Anne-Mari Mustonen; Raija Tammi; Markku Tammi; Petteri Nieminen (Journal of Comparative Physiology B, 2014)

The heparan sulfate editing enzyme Sulf1 plays a novel role in zebrafish VegfA mediated arterial venous identity - Bushra Gorsi; Feng Liu; Xing Ma; Timothy J. A. Chico; Ashok Shrinivasan; Kenneth L. Kramer; Esther Bridges; Rui Monteiro; Adrian L. Harris; Roger Patient; Sally E. Stringer (Angiogenesis, 2014)

Numerical Simulation of the 2011 Tohoku Tsunami Based on a New Transient FEM Co-seismic Source: Comparison to Far- and Near-Field Observations - Stephan T. Grilli; Jeffrey C. Harris; Tayebeh S. Tajalli Bakhsh; Timothy L. Masterlark; Christodoulos Kyriakopoulos; James T. Kirby; Fengyan Shi (Pure and Applied Geophysics, 2013)

Physicochemical assessment and phosphorus storage of canal sediments within the Everglades Agricultural Area, Florida - Jaya Das; Samira H. Daroub; Jehangir H. Bhadha; Timothy A. Lang; Orlando Diaz; Willie Harris (Journal of Soils and Sediments, 2012)

Potential climatic transitions with profound impact on Europe - Anders Levermann; Jonathan L. Bamber; Sybren Drijfhout; Andrey Ganopolski; Winfried Haeberli; Neil R. P. Harris; Matthias Huss; Kirstin Krüger; Timothy M. Lenton; Ronald W. Lindsay; Dirk Notz; Peter Wadhams; et al. (Climatic Change, 2012)

The Business of Forest Enterprise / Urban Ecosystems - Steve Narolski; Richard Bin Mei; Rafael De La Torre; Mike Clutter; John Pait; Maggi Kelly; Frederick Cubbage; Patricio MacDonagh; Gustavo Balmelli; Virginia Morales Olmos; Adriana Bussoni; Rafael Rubilar; et al. (Journal of Forestry, 2011)
22In 2009, five unique methods were used to inspect vegetation-related conditions along Bonneville Power Administration (BPA) rights-of-way (ROW). Some methods were trials that BPA committed to execute as part of a settlement with its regional regulatory organization, the Western Electric Coordination Council (WECC), for violations of reliability standards from vegetation grow-in related outages. A combination of simple, stratified, and 100% sampling were used to compare and contrast each inspection technique. A cost-replacement comparison between all inspection techniques was performed, weighting efficacy of one technique to another in the form of replacement value. Cost-benefit and return-on-investment analyses were also computed. From these analyses, LiDAR proved most effective in identifying vegetation related clearance issues but proved most costly, at least for initial establishment. The average cost of LiDAR trended downward with subsequent flights. The most cost effective method was using helicopters with either Natural Resource Specialists (NRS) or Transmission Line Maintenance (TLM) personnel serving as aerial observers, but this methodology proved the most inaccurate. Furthermore, the ancillary utility of LiDAR for related asset assessments more than justify the initial expense, includes power line sag ratings, asset (structures, insulators, roads, etc.) health, and encroachment identification. It is hypothesized that incorporating LiDAR sampling from 20% of the whole system per year to 40+ % may actually represent a cost-savings when allocating available resources system-wide. This data can also be used for documenting compliance with all federal regulations and requirements, as well as substitute for manual on-the-ground inspections, whether by BPA staff or third-party contractors.

Erratum to: The Effect of Pulsatile Flow on Intrathecal Drug Delivery in the Spinal Canal - H. D. M. Hettiarachchi; Ying Hsu; Timothy J. Harris; Richard Penn; Andreas A. Linninger (Annals of Biomedical Engineering, 2011)

The Effect of Pulsatile Flow on Intrathecal Drug Delivery in the Spinal Canal - H. D. M. Hettiarachchi; Ying Hsu; Timothy J. Harris; Andreas A. Linninger (Annals of Biomedical Engineering, 2011)

Hybridization and polyploidy as drivers of continuing evolution and speciation in Sorbus - ASHLEY ROBERTSON; TIMOTHY C. G. RICH; ALEXANDRA M. ALLEN; LIBBY HOUSTON; CAT ROBERTS; JON R. BRIDLE; STEPHEN A. HARRIS; SIMON J. HISCOCK (Molecular Ecology, 2010)

Atmospheric Measurements of HONO by Tunable Diode Laser Absorption Spectroscopy - C. L. Schiller; S. Locquiao; Timothy J. Johnson; G.W. Harris (Journal of Atmospheric Chemistry, 2001)